Perlindungan Hukum Terhadap Konsumen Makanan Impor Tanpa Izin Edar Yang Dijual Melalui Aplikasi Shopee - Alda Meydiyana Sagita; Arikha Saputra (Ajudikasi : Jurnal Ilmu Hukum, 2022)
Imported food is a processed food originating from abroad which is widely sold through e-commerce, one of which is shopee, the needs and demands of the public, especially in Indonesia for imported food products, make business actors continue to increase the number of products and variations of imported food products traded. However, many imported foods sold through e-commerce shopee do not have a distribution permit from BPOM. Therefore, it is necessary to protect the rights of consumers of imported food as regulated by Law Number 8 of 1999 concerning Consumer Protection. Writing this scientific journal aims to increase understanding of the importance of legal rules that protect consumers on imported food without a distribution permit and to know the form of supervision carried out by BPOM Semarang City on imported food sold through e-commerce shopee. This study uses a normative juridical legal research method with a statutory approach and a fact approach. The types of data and sources used in the research are primary data in the form of direct interviews with BPOM Semarang City in the field of prosecution and secondary data in the form of laws and regulations, books, journals and research results. From the results of the study, it can be concluded that the implementation of legal protection for consumers for imported food products sold through shopee e-commerce has not been effectively implemented because there are still many imported food products without a BPOM distribution permit that are sold through shopee e-commerce and do not comply with security requirements. to be consumed. The requirement for security is in the form of an obligation to have a distribution permit, which is in accordance with Article 91 paragraph (1) of Law Number 18 of 2012 concerning Food which states "In terms of supervision of safety, quality and nutrition, any processed food made domestically or imported for traded in retail packaging, food business actors are required to have a distribution permit”. This is in line with the policy contained in Shopee's e-commerce that it is not allowed to have food without a distribution permit in accordance with the policies that have been applied to the list of prohibited goods and are limited in point (iv) which reads "food and beverages that endanger the safety of its users, or not. having a distribution permit from the Food and Drug Supervisory Agency (BPOM) the seller is not allowed to register food and food-related goods on the shopee site", in addition to the policy given by shopee, BPOM will also carry out Cyber ​​Patrol supervision.